Auricular points acupressure for insulin resistance in overweight/obese women with polycystic ovary syndrome: protocol for a randomised controlled pilot trial. Issue 5 (28th May 2019) - Li, Yan; Hou, Lihui; Wang, Yingji; Xie, Liangzhen; Zhang, Meiwei; Pan, Zimeng; Li, Yangyang; Ding, Yicheng; Sun, Miao; Qu, Yufang; Liu, Songjiang
Abstract : Introduction: Approximately 5%–20% of reproductive women suffer from polycystic ovary syndrome (PCOS). Auricular points acupressure (AA) may serve as alternative management for PCOS for its benefits in both physical and psychological well-being. However, the effects of AA for insulin resistance (IR) in overweight/obese PCOS women have not been confirmed. Methods and analysis: The present study is designed as a randomised, placebo-controlled pilot trial to evaluate the effectiveness and safety of AA in treating IR in women with PCOS. A total of 60 eligible PCOS subjects will be randomised into an intervention group (AA group) and a control group (sham AA group) in a ratio of 1:1. Magnetic beads will be taped to the auricular points by the same senior acupuncture specialist from the First Affiliated Hospital, Heilongjiang University of Chinese Medicine. The treatment will last for 12 weeks. Primary outcome measure will be changes in homeostasis model assessment of IR between baseline and after 3 months of AA/sham AA treatment. Secondary outcomes include hormonal profile, weight, waist/hip circumference, body mass index, blood pressure, Ferriman-Gallwey score, acne and the assessment of health-related quality of life. Outcome measures are collected at baseline and the end of treatment visit. Ethics and dissemination: The protocol has been approved by the ethics committee of the First Affiliated Hospital of Heilongjiang University of Chinese Medicine (HZYLLKY201800301). Written informed consent will be obtained from all participants. The results will be disseminated through peer-reviewed journals for publications. Trial registration number: NCT03546595 ; Pre-results.